Analisis Psikometrik Skala Ucla Loneliness pada Mahasiswa di Sumatera Barat - Yodi Kasinda; Muhammad Wahyudi; Shaztry Zalmy; Nur Fhadilla Alfanissa S; Niken Wulandari; Citra Rahma Deya; Mario Pratama (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Loneliness is a psychological condition that arises due to a mismatch between expected and existing social relationships. This study aims to test the validity and reliability of the UCLA Loneliness Scale version 3 in measuring loneliness in college students in West Sumatra. A total of 200 active college students became participants selected through purposive sampling techniques. Data were collected using an online questionnaire and analyzed using the Cronbach's Alpha reliability test and exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The results showed that this scale has very high reliability (α = 0.955), as well as adequate item discrimination power (0.491–0.791). EFA identified two main factors, namely social loneliness and emotional loneliness, which were then confirmed through CFA with good model fit values (RMSEA = 0.079; SRMR = 0.049; GFI = 0.924). These findings support the two-dimensional structure of the loneliness construct and indicate that the UCLA Loneliness Scale version 3 is suitable for use in the Indonesian cultural context. This scale has the potential to be applied in psychological screening and campus-based interventions to address loneliness among college students.